Managing diseases in cucurbits – the eco-friendly way - Maheshwari, S K; Choudhary, B R (Indian Horticulture, 2019)
Vegetables constitute an important component of Indian diet. Of several vegetable groups, cucurbitaceous vegetables find special place among consumers in western Rajasthan. Cucurbitaceous crops are one of the important vegetable crops from nutritional as well as economic point of view. Cucurbits contribute 10.80% and 5.43% of total area and production of vegetables, respectively in Rajasthan (2016-17).